Developing and managing engineering procedures : concepts and applications - Cloud, Phillip A. (Noyes Publications ; William Andrew Pub., 2001)
This book provides hands-on techniques for writing engineering procedures to achieve ISO 9000 compliance.
Keywords: ISO 9000 Series Standards.; Engineering -- Management.; Standards, Engineering.; elektronické knihy; electronic books